Pengaruh Implementasi Hukum Acara Pidana Terhadap Perlindungan Hak Asasi Tersangka dalam Proses Peradilan - Syahda, Voleta Sela (CV WAHANA PUBLIKASI, 2023)
The enforcement of criminal procedure law plays an important role in maintaining the balance between the interests of the state and the protection of the human rights of suspects in the judicial process. The legal issue that often arises is the misalignment between the implementation of criminal procedure law and the protection of suspects’ human rights, especially in terms of arrest, detention, and trial. This paper aims to analyze the effect of the implementation of criminal procedure law on the protection of the human rights of suspects at various stages of the judicial process. The writing method used is normative juridical, with a legislative approach as well as literature and case studies. The results showed that although the criminal procedure law has expressly regulated the protection of the human rights of suspects, in practice there are still many violations, such as abuse of authority by law enforcement officials and lack of understanding of the rights of suspects. This indicates the need for reforms in the enforcement of criminal procedure law to be more effective in protecting the human rights of suspects, including increased supervision and education of legal officers and simplification of the legal process.